The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.22219/jaa.v3i2.14003
|View full text |Cite
|
Sign up to set email alerts
|

Hambatan Penerapan Sanksi Pajak Di KPP Pratama Pamekasan

Abstract: This research aims to illustrate how the processes/procedures and obstacles in the implementation of tax sanctions in KPP Pratama Pamekasan. The research method used is a case study approach. One key informant with two supporting informants, then the information was analyzed using the Miles and Huberman model consisting of data reduction, data presentation, conclusion drawing, and verification. The result of this research was first, the application of tax sanctions in KPP Pratama Pamekasan only applied to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Individuals who are not tax compliant may make external attributions, i.e. they consider that their non-compliant behavior is caused by external factors such as the difficulty of understanding tax regulations or the lack of supervision from the government Tax Compliance in Indonesian MSMEs: Key Factors Explored Fakultas Ekonomi, Universitas Muhammadiyah Cirebon | 155 (Yaqin & Alwiyah, 2020). In the context of tax compliance, internal attributions related to Intrinsic motivation to comply may encourage individuals to remain compliant with their tax obligations.…”
Section: Literature Review and Hypotheses Development Attribution Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who are not tax compliant may make external attributions, i.e. they consider that their non-compliant behavior is caused by external factors such as the difficulty of understanding tax regulations or the lack of supervision from the government Tax Compliance in Indonesian MSMEs: Key Factors Explored Fakultas Ekonomi, Universitas Muhammadiyah Cirebon | 155 (Yaqin & Alwiyah, 2020). In the context of tax compliance, internal attributions related to Intrinsic motivation to comply may encourage individuals to remain compliant with their tax obligations.…”
Section: Literature Review and Hypotheses Development Attribution Theorymentioning
confidence: 99%
“…Tax sanctions applied to non-compliant MSME actors can be fines or block access to banking facilities or public services. Research conducted on MSME actors in Indonesia found that the existence of tax sanctions significantly influences tax compliance (Sinaga, 2017;Yaqin & Alwiyah, 2020). MSMEs that are aware of the consequences of tax violations, such as fines or blocking access, tend to be more compliant in fulfilling their tax obligations.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the motivations for tax avoidance are influenced by individualism, masculinity, uncertainty, and power distance which are inversely proportional to tax avoidance actions that occur in entities (Amalia & Handayani, 2019;Yoo & Lee, 2018, so that an increase in some of these factors can be a solution to mitigate the occurrence of tax avoidance. Tax evasion is caused by taxpayers' non-compliance with tax regulations that are influenced by sanctions, audits, perceptions, awareness, knowledge, and services (Famami & Norsain, 2019), which is exacerbated by the condition that the application of tax sanctions is still not optimal (Yaqin & Alwiyah, 2020). So that the possibility of audits or low public services by the government is also a motivating factor for tax avoidance.…”
Section: Introductionmentioning
confidence: 99%